Selectfluor and alcohol-mediated synthesis of bicyclic oxyfluorination compounds by Wagner–Meerwein rearrangement - Dağalan, Ziya; Çelikoğlu, Muhammed Hanifi; Çelik, Saffet; Koçak, Ramazan; Nişancı, Bilal (Beilstein Journal of Organic Chemistry, 2024)
Herein, we report the first environmentally friendly systematic fluoroalkoxylation reactions in bicyclic systems. New oxyfluorination products were obtained with excellent yields (up to 98%) via Wagner–Meerwein rearrangement using benzonorbornadiene and the chiral natural compound (+)-camphene as bicyclic alkenes, selectfluor as an electrophilic fluorine source, and water and various alcohols as nucleophile sources. The structure of bicyclic oxy- and alkoxyfluorine compounds was determined by NMR and QTOF-MS analyses.
Keywords: alkoxyfluorine compounds; bicyclic alkene; oxyfluorination; selectfluor; Wagner–Meerwein rearrangement